A goblet cell carcinoma of the appendix presenting as an acute appendicitis: a case report. Issue 2 (3rd March 2020) - Coevoet, D.; Maenhoudt, W.; Beaurang, J.; Bontinck, J.; Lockefeer, F.; Vandenabeele, L.; Rondou, T.; Bontinck, H.
Abstract: Background : A goblet cell carcinoma of the appendix is a rare neoplasm with histological features of both adenocarcinomas and carcinoid tumours. It has a more aggressive behaviour in comparison to the more common classic neuroendocrine appendiceal tumours. Clinical presentation is variable and a significant proportion of patients present with an acute appendicitis. The aggressive evolution of these tumours makes the management more challenging. Case report : We report the case of a 43-year-old man with acute right iliac fossa pain who was initially diagnosed with an acute appendicitis. Histological analysis of the resected appendix demonstrated the presence of a goblet cell carcinoma with perineural and lymphovascular invasion. No distant metastasis was present. A right hemicolectomy was performed and adjuvant chemotherapy was administered. Conclusion : Goblet cell carcinomas is a distinct entity which should be delineated from the classical appendiceal carcinoids. Its clinical evolution obliges a more aggressive therapeutic strategy.